2017
DOI: 10.4067/s0718-58392017000300187
|View full text |Cite
|
Sign up to set email alerts
|

Mexican native tomatoes as rootstocks to increase fruit yield

Abstract: these traits. The accessions LOR-22, LOR-77, LOR-81, LOR-84, LOR-95 and LOR-100 with the hybrid 'El Cid', and LOR-81, LOR-84 and LOR-100 with the hybrid 'Sun 7705', increased significantly yield by 19% and 22%, respectively, compared to ungrafted control. Moreover, characteristics related to fruit quality were preserved with grafting. The best combination scion/rootstock ('Cid'/100) yielded 30% higher than hybrid 'El Cid' without grafting and 16% higher than the commercial rootstock 'Multifort'. This allowed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
2
5
0
2
Order By: Relevance
“…The use of grafts affected the productive variables Table 3, where the weight of fruits, number of fruits, and polar diameter increased, the results agree with those obtained by Velasco-Alvarado et al (2019) where grafted plants obtained a yield of 7.4 kg per plant, the yield stood out with 19% compared to the plants without grafting 6.2 kg per plant. Fruit weight was influenced by rootstock, but it was not affected by grafting Ergun and Aktas (2018) reported that when using bell pepper grafts it produced about 12% more yield than the control plant without grafting.…”
Section: Discussionsupporting
confidence: 82%
“…The use of grafts affected the productive variables Table 3, where the weight of fruits, number of fruits, and polar diameter increased, the results agree with those obtained by Velasco-Alvarado et al (2019) where grafted plants obtained a yield of 7.4 kg per plant, the yield stood out with 19% compared to the plants without grafting 6.2 kg per plant. Fruit weight was influenced by rootstock, but it was not affected by grafting Ergun and Aktas (2018) reported that when using bell pepper grafts it produced about 12% more yield than the control plant without grafting.…”
Section: Discussionsupporting
confidence: 82%
“…Lycopersicoides ) were used. A database was built with information from scientific reports and articles [ 36 , 51 , 52 , 53 , 54 , 55 ] and national (World Biodiversity Information Network) [ 56 ] and international plant inventories (Tomato Genetics Resource Center, Global Biodiversity Information Facility, Solanaceae source) [ 21 , 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mexico as the place of final domestication of the tomato provides a high diversity of genetic resources of wild and native tomato varieties that allow discovering abiotic stress tolerance traits, including salt tolerance (Blanca et al, 2012;Velasco-Alvarado et al, 2017). Before the release of the first commercial tomato hybrid cultivar in 1946, breeding was performed with open pollinated varieties which could be considered landraces or heirlooms (Bai and Lindhout, 2007).…”
Section: Academicpresmentioning
confidence: 99%
“…These tomatoes are sold regionally and vary widely in shape, size, flavor and names. Velasco-Alvarado et al (2017) classified some of these traditional native varieties according to fruit size and shape. There have been recent attempts to describe the agronomic diversity of Mexican native landraces from the states of 'Oaxaca' and 'Puebla' in regard to total soluble solids and yield, among other parameters.…”
Section: Academicpresmentioning
confidence: 99%